UNIT 2.16 iRegulon and i‐cisTarget: Reconstructing Regulatory Networks Using Motif and Track Enrichment. Issue 1 (17th December 2015) - Verfaillie, Annelien; Imrichova, Hana; Janky, Rekins; Aerts, Stein
Abstract : Gene expression profiling is often used to identify genes that are co‐expressed in a biological process or disease. Downstream analyses of co‐expressed gene sets using bioinformatics methods can reveal candidate transcription factors (TF) that co‐regulate these genes, based on the presence of shared TF binding sites. Drawing gene regulatory networks that connect TFs to their predicted target genes can uncover gene modules that implement a particular function. Here, we describe several protocols to analyze any set of co‐expressed genes using iRegulon and i‐cisTarget. These tools perform regulatory sequence analysis (motif discovery) and integrate and mine large collections of existing regulatory data, such as ChIP‐Seq, DHS‐seq, and FAIRE‐seq (track discovery). While iRegulon focuses on sets of co‐expressed genes, i‐cisTarget also analyses genomic regions as input. The following protocols describe how to install and use these tools, how to interpret the obtained results, and will thus help to create meaningful regulatory networks. © 2015 by John Wiley & Sons, Inc.